Flexible Working Practices for Educated Egyptian Women in the Digital Era: A Study on Telework during the COVID-19 Pandemic and Its Potential to Reduce Gender Gap - El Ashry, Sarah Sherif (AUC Knowledge Fountain, 2022)
Telework has recently gained popularity around the world, a trend that saw significant growth with the emergence of the COVID-19 pandemic. Egypt is one of the many countries that adopted this new approach in an attempt to facilitate social distancing policies. This allowed more working mothers in Egypt to experience telework practices for the first time and be able to report their experience. These circumstances have presented a great opportunity to test its simultaneous application across different sectors throughout Egypt. Therefore, it is important to reflect on the adoption of telework during the COVID-19 pandemic. This study aims to examine the effects of applying flexible work techniques, telework specifically, on educated mothers in Egypt as a means to solve the persistent conflict between the responsibilities of motherhood and professional career life. Moreover, the study highlights the importance of Information and Communication Technology (ICT) and proper regulations to ensure the successful implementation of telework and to potentially achieve the following outcomes, including a reduction in unemployment rates, the empowerment of women, and shrinking the gender gap. Primary data were collected through qualitative one-to-one semi-structured interviews with mothers and managers. The findings have been divided into three main themes following the conceptual framework of the study. This includes the drivers that act as motivators for adopting telework. These include variables such as demographics, processes such as technology, and outcomes including a decrease in unemployment. The study suggests a number of recommendations that address the interests of stakeholders; including mothers, organizations and the government.